Role of inflammation and the NF-κB signaling pathway in Hirschsprung’s disease - Elkrewi, Enas; Abdulqader, Ahmad Abdulrahman A. al-; Khasanov, Rasul; Maas-Omlor, Silke; Boettcher, Michael; Wessel, Lucas; Schäfer, Karl-Herbert; Tapia-Laliena, María Angeles (Biomolecules, 2024)
Hirschsprung’s disease (HSCR, incidence 1/5000 live births) is caused by the failure of neural crest-derived precursors to migrate, survive, proliferate, or differentiate during the embryonic development of the Enteric Nervous System (ENS), which could be disrupted by many factors, including inflammatory processes. The NF-κB family controls several biological processes, including inflammation, neurogenesis, and cell migration. With the aim of studying the potential role of NF-κB in HSCR, we have analyzed the expression of the NF-κB main subunits and other NF-κB-related genes by RT-qPCR in HSCR tissue samples (sub-divided into ganglionic and aganglionic segments). We found decreased gene expression of the NF-κB main subunit RELA but also of NFKBIA, TNFA, TFGBR2, and ERBB3 in the pathologic distal aganglionic segments compared to the proximal ganglionic segments. Moreover, we could also confirm the lower protein expression of RelA/p65 in the aganglionic distal segments by immunofluorescence staining. Further, we show that the expression of RelA/p65 protein in the proximal segments concurs with lymphocyte infiltration in the bowel tissue, indicating a pro-inflammatory activation of p65 in the proximal ganglionic HSCR tissue in the patients analyzed. All in all, our findings suggest that the modulation of NF-κB signaling in the neuro-enteric system does obviously contribute to the pathological effects of HSCR.
Gesehen am 18.02.2025